Business Legality and Halal Labeling in MSME Sales Volume - Moh. Ma‘ruf; Riyan Sisiawan Putra; Anusuiya Subramaniam; Tri Siwi Agustina; Dwi Novitasari; Feri Ihsan Muzaki; Ana Lailatul Fitriya (Academia Open, 2026)
General Background: Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in economic stability and development, particularly in Indonesia where they significantly contribute to employment and GDP. Specific Background: In Sidoarjo Regency, increasing competition among MSMEs with similar products has led to fluctuating sales volumes and reduced customer loyalty. Knowledge Gap: Despite the importance of regulatory compliance and religious assurance, limited empirical evidence explains how business legality and halal labeling relate to MSME sales performance at the local level. Aims: This study aims to examine the relationship between business legality, halal labeling, and sales volume of MSME products in Sedati District, Sidoarjo Regency. Results: Using a quantitative survey with 79 respondents and multiple linear regression analysis, the findings indicate that both business legality and halal labeling show significant relationships with sales volume, supported by partial (t-test) and simultaneous (F-test) significance results. Novelty: This study provides localized empirical evidence integrating regulatory and religious product attributes within MSME sales analysis in a specific Indonesian district context. Implications: The findings highlight the importance for MSME actors to prioritize legal compliance and halal certification to strengthen consumer trust and support sales performance in competitive markets. Highlights: Legal compliance and certified product status are statistically linked to higher product demand levels. Religious assurance attributes contribute to purchasing decisions in predominantly Muslim markets. Combined regulatory and certification factors are associated with measurable variations in product turnover. Keywords: Business Legality, Halal Labeling, Sales Volume